An agent-based framework for simulating contractors’ safety behavior - Awwad, Rita (2017)
A contractor’s attitude towards construction safety, and the subsequently implemented safety program, are complex phenomena that are affected by a wide array of factors. These factors can range from government policy and insurance companies’ builder’s risk models on one end of the spectrum, to social and cultural factors on the other end. Predicting the safety behavior of contractors is a difficult task, even when government labor safety policies and builder’s risk insurance programs are well established. In regions where government safety legislation is non-existent, insurance companies lack the mechanisms to track the safety performance of contractors, and the cultural climate promotes safety negligence; predicting the safety behavior of contractors requires intricate and complex modeling of the entire environment in which these contractors operate and evolve. A conceptual framework for an agent-based model is presented that allows the analysis of how initiatives taken by different stakeholders in the construction environment can affect the safety behavior of contractors. The model is tested on a case study, and the behavior of various agents and their interactions are summarized. The resulting model is shown to be promising for use by decision makers to find optimal strategies aiming at improving the construction market’s safety performance - See more at: http://ascelibrary.org/doi/abs/10.1061/9780784479827.267#sthash.Lse7L12g.dpuf